Incentive spirometry as a way to prevent pulmonary atelectasis development - Kuzmenko, T. S.; Vorotyntsev, S. I. (Zaporozhye Medical Journal, 2019)
The purpose. The purpose of this study was to evaluate the effectiveness of incentive spirometry (IS) as a method of atelectasis prevention in patients with moderate or high risk of PPCs development after upper abdominal surgery. Materials and methods. The study consisted of two stages. The first retrospective stage was to analyze the medical histories data of 51 inpatients, who were included in the comparison group. The prospective part of the study included 39 patients of the study group, who had sessions of the IS during the first 7 days of the postoperative period. Patients of both groups were operated on the upper abdominal organs by open procedure, operation time was more than 2 hours, all patients had an ARISCAT score ≥26 points. Pulmonary atelectasis development was monitored in the groups in the first week of the postoperative period. The statistical analysis of the data was performed using the Microsoft Excel 2013 and Statistica for Windows 6.0 programs. When comparing the groups according to the clinical outcome, the relative risk (RR) and odds ratio (OR) were determined and then confidence intervals (95 % CI) were calculated. Statistical significance of the results was determined depending on the CI values. Results. During the first 7 days, 34 cases of pulmonary atelectasis (67 %) were recorded in the comparison group. In the study group, 9 patients (23 %) were diagnosed with pulmonary atelectasis. The analysis of clinical results showed that when applying incentive spirometry, there was a statistically significant decrease in the relative risk of atelectasis development within the first week of the postoperative period (RR = 0.346, 95 % CI [0.189; 0.634], P = 0.0006). The odds ratio of atelectasis development in the study group was statistically lower than in the group of retrospective study (OR = 0.150, 95 % CI [0.058, 0.386], P = 0.0001). Conclusions. Incentive spirometry is an effective way to prevent pulmonary atelectasis in patients with a moderate or high risk for developing postoperative pulmonary complications according to the ARISCAT scale after upper abdominal surgery.